Identification and Characterization of DNA Demethylase Genes and Their Association With Thermal Stress in Wheat (Triticum aestivum L.) - Gahlaut, Vijay; Samtani, Harsha; Gautam, Tinku; Khurana, Paramjit (Frontiers in Genetics, 2022)
DNA demethylases (dMTases) are essential proteins in plants that regulate DNA methylation levels. The dMTase genes have been explored in a number of plant species, however, members of this family are not reported in wheat. We identified 12 wheat dMTase genes divided into two subfamilies, repressor of silencing 1 (ROS1) and DEMETER-Like (DML). The TadMTases in the same subfamily or clade in the phylogenetic tree have similar gene structures, proteins motifs and domains. The promoter sequence contains multiple cis-regulatory elements (CREs) that respond to abiotic stress, hormones, and light, suggesting that the majority of TadMTase genes play a role in wheat growth, development, and stress response. The nuclear localization signals (NLSs) and subcellular localization, and SRR motifs were also analyzed. The expression profiles analyses revealed that TadMTase genes showed differential gene expression patterns in distinct developmental stages and tissues and under heat stress (HS). Furthermore, the qRT-PCR analysis revealed that TadMTase gene expression differed amongst wheat cultivars with varying degrees of HS tolerance. Overall, this work contributes to the understanding of the biological function of wheat dMTases and lays the foundation for future investigations.